FUN AEROBIC DAN EDUKASI KESEHATAN MENGENAI AKTIVITAS FISIK DAN KONSUMSI MAKANAN BERGIZI DI SD LAZUARDI CORDOVA GCS, JAKARTA BARAT - Mustikawati, Intan Silviana; Kuswari, Mury; Nuzrina, Rachmanida; Pamungkas, Rian Adi; Rosya, Ernalinda; Eff, Aprilita Rina Yanti; Rahayu, Sri Teguh (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
One of the problems of school-age children is a change in lifestyle from traditional life style to sedentary life style which is the cause of lack of physical activity that can increase the risk of obesity. The practice of regular physical activity is very important to improve body health which can have an impact on student achievement. Communication, information, and education among students about the importance of practicing regular physical activity are needed to improve knowledge, attitudes, and practices of physical activity. The purpose of this activity is to provide health education about physical activity and consumption of nutritious food, practice aerobic gymnastics together, and health examinations and consultations. The targets of this activity are students, parents, teachers, and employees of SD Lazuardi Cordova GCS, West Jakarta. These activities were carried out in the form of health education through lectures and discussions, practice aerobic gymnastics together, health checks such as height, weight, blood pressure, nutritional status, blood sugar, and uric acid, as well as health consultations. Regular health education in schools is needed to improve health knowledge, attitudes, and practices in students.